PENGARUH KEPEMILIKAN MANAJERIAL DAN KEBIJAKAN HUTANG TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi Empiris Pada Perusahaan Manufaktur Sektor Konsumsi Sub-Sektor Pengolahan Makanan Yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - dewi, eka kusuma; Romadhina, Anggun Putri (LPPM Universitas Putera Batam, 2024)
The definition of Corporate Social Responsibility can be seen in Law number 40 of 2007 concerning Limited Liability Companies (UUPT) article 1 paragraph 3 states that social and environmental responsibility is the company's commitment to participate in sustainable economic development in order to improve the quality of life and a beneficial environment, both for the company itself, the local community and society in general. CSR emerged as a result of the modernization of society which already understands that activities carried out by companies can have a negative impact on the environment. Moreover, this is very close to the activities carried out by manufacturing companies because manufacturing companies are the companies that interact the most with the public. Factors that influence CSR disclosure in this research are managerial ownership and debt policy. This type of research uses quantitative research using secondary data in the form of company annual reports taken from the non-cyclical consumer sector, food processing subsector listed on the Indonesia Stock Exchange for the period 2017 to 2021. The sampling method uses purposive sampling. From the research results, it is proven that managerial ownership does not influence CSR disclosure and conversely debt policy influences CSR disclosure. Meanwhile, simultaneously, managerial ownership together with debt policy influence CSR disclosure.